ACUTE NARCOTIC DRUG INTOXICATIONS: ETIOLOGY, SEX/AGE DISTRIBUTION AND CLINICAL OUTCOME - Petko Marinov; Snezha Zlateva; Georgi Bonchev; Dobri Ivanov; Kaloyan Georgiev; Yulichka Sabeva; Marieta Yovcheva (Peytchinski Publishing, 2017)
Purpose: Poisoning with drugs is a serious medical and social problem worldwide. Retrospective analysis of acute poisoning with narcotic drugs had been performed in Varna region for 25 years (1991-2015). Material and Methods: The number of patients received hospital treatment after poisonings with narcotic substances was 677, which represented 3.9% of all acute exogenous intoxications. Results: Narcotic poisonings were more common in men - 546 (80.6%), than in women - 131 (19.4 %). The ratio male/ female was 4.17:1. The largest number of intoxications were in the age group up to 24 years - 1123 (66%), and only 2.65% of patients were over 45 years. Death was registered in 6 (0.9%) patients.